Pulmonary Metastasectomy of Sarcoma: Is the Ratio of Surgical Margin to Nodule Size a Prognostic Factor? - Özdil, Ali; Tekneci, Ahmet Kayahan; Dökümcü, Zafer; Divarcı, Emre; Keçeci, Burçin; Sezak, Murat; Çakan, Alpaslan; Çağırıcı, Ufuk (The Thoracic and Cardiovascular Surgeon, 2019)
Background Main prognostic factors of improved survival after pulmonary metastasectomy (PM) for osteogenic and soft tissue sarcomas are suggested as histological type, number and size of pulmonary nodules, and disease-free interval (DFI).Methods Sixty-nine patients who underwent PM between January 1999 and December 2017 were evaluated retrospectively. Relations between parameters and prognostic risk factors for overall survival (OS) and disease-free survival (DFS) were evaluated.Results Osteosarcoma was the most common histologic type (36.2%) and 21 of 25 cases were seen under the age 20 years (p < 0.001). Comparison of patient groups including osteosarcoma and nonosteosarcoma patients showed significant difference according to age (p < 0.001), nodule size (p = 0.033), ratio of surgical margin to nodule size (p = 0.007), and DFI (p = 0.039). Univariate analysis showed that the number of nodules (p = 0.008), ratio of surgical margin to nodule size (p = 0.001), and localization of nodule (p = 0.039) were significant factors associated with DFS. Also, nodule size (p = 0.042), number of nodules (p = 0.003), ratio of surgical margin to nodule size (p < 0.001), and laterality (p = 0.027) were significant prognostic factors associated with OS. Cut-off values of ratio of surgical margin to nodule size for DFS and OS were calculated as 0.94. Logistic regression analysis determined the ratio of surgical margin to nodule size as the common significant risk factor for DFS and OS.Conclusions Our study showed that the ratio of surgical margin to nodule size ≥ 1 should be taken as a common risk factor for DFS and OS. Therefore, resection of nodules with the possible widest surgical margin is an important point of PM.
Keywords: pulmonary metastasectomy; sarcoma; survival; prognostic factor